Roman Period Stone Vessels at Syedra - Mustafa Yıldızlı (Höyük, 2023)

(untitled)
Syedra was important in Antiquity as a port city and a residential area on the sheltered summit. It is understood from the inscriptions, finds, and structures that the settlement continued to the town from the 9th century BC to the 12th century AD, but the city’s golden age was 2. and 4. centuries AD. In this study, 28 stone vessels were evaluated. Stone vessels were used extensively in agoras, baths, houses, and shops in Roman Age. Mortars, pestles, shallow vessels, plates, and bowls are among the stone vessels found in Syedra. Mortars constitute the densest group of finds. Since they are an auxiliary tool used with the mortar, pestles constitute the second most dense group of finds. These artifacts show that people of Late Antiquity produced stone vessels and used them mainly in food culture. In addition to this use, these containers were also used to produce pharmaceuticals and cosmetic products, and shallow containers were preferred for cleaning. It is thought that the deep mortars found in the city may have been used to produce olive oil or wine. As can be understood from here, deep mortars were preferred in the industrial area. Stone vessels were among the gifts offered to the dead in Late Antiquity. The mortars in Chamber Tombs I and II are essential in showing that these vessels may have been left in the graves as burials. Moreover, the two unfinished artifacts indicate the existence of production in the city and, therefore, a workshop. Stone vessels found at Syedra are dated between the 2nd and 6th centuries AD.